2022
DOI: 10.3311/pptr.20076
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Damper Force Estimation for Automotive Suspension

Abstract: The real-time knowledge of the damper force is of paramount importance in controlling and diagnosing automotive suspension systems. This study presents a generalized H2/LPV observer for damper force estimation of a semi-active electro-rheological (ER) suspension system. First, an extended quarter-car model augmented with the nonlinear and dynamical model of the semi-active suspension system is written into the quasi-LPV formulation. Then, the damper force estimation method is developed through a generalized H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The works of these authors deserve attention when considering the effect of vehicle track excitations in conjunction with a spatial contact model that accounts for the interaction between the contact wire and the pantograph strip (Song, et al, 2021b). Several researchers have reported that mathematical modeling proved to be an effective approach in capturing the complex dynamic behavior of the pantograph system because of the high cost of field testing (Pham et al, 2022;Song and Li, 2021;Yu et al, 2021). However, it is found that the dynamic behavior of the pantograph system is limited when vehicle-track disturbances are considered.…”
Section: Introductionmentioning
confidence: 99%
“…The works of these authors deserve attention when considering the effect of vehicle track excitations in conjunction with a spatial contact model that accounts for the interaction between the contact wire and the pantograph strip (Song, et al, 2021b). Several researchers have reported that mathematical modeling proved to be an effective approach in capturing the complex dynamic behavior of the pantograph system because of the high cost of field testing (Pham et al, 2022;Song and Li, 2021;Yu et al, 2021). However, it is found that the dynamic behavior of the pantograph system is limited when vehicle-track disturbances are considered.…”
Section: Introductionmentioning
confidence: 99%